Determination of some physical properties of common Malaysian rice MR219 seeds - Bashar, Zubairu Usman; Wayayok, Aimrun; Mohd Soom, Mohd Amin (Southern Cross Publishing, 2014)
Knowledge on physical properties of seeds is an important tool for designing agricultural machines and other equipment to handle planting, harvesting, processing, packaging and storing. The most common rice variety grown in Malaysia is MR219 but the data on its physical properties is still lacking. The aim of this study was to determine the effect of moisture content on the physical properties (basic dimensions, porosity, bulk and true densities, coefficient of friction, repose angle and sphericity) of MR219 rice variety. These properties were evaluated as a function of moisture content at 14.26, 18.94 and 22.50% dry basis. The results revealed that length, width and thickness increased from 9.639 to 10.187, 2.266 to 2.2416 and 1.878 to 2.038mm, respectively with increasing moisture content from 14.26 to 22.50%. Similarly,1000 seed mass (M1000) increased from 27.06 to 29.88g as well as arithmetic and geometric mean diameters from 4.85 to 4.88 and 3.44 to 5.68 mm. Bulk density, sphericity, and surface area have reported increase with increasing moisture content from 517.70 to 543.544kg/m3 , 0.358 to 0.362% and 37.203 to 42.596mm2, respectively. A decrease was observed for true density (1244.571 to 1197.488kg/m3 ) and porosity (58.403 to 54.610) as seeds rewetting increased. The static coefficient on three surfaces, namely PVC, plywood and aluminum showed increase on PVC and aluminum from 0.356 to 0.387 and 0.309 to 0.324 but a decrease on plywood from 0.372 to 0.341, respectively. This technical information is useful to design the machines for handling MR219 rice seeds.